Principles and Practicalities of ENT : How to approach common clinical scenarios - Gupta, Keshav K.; Vatish, Divya; Jolly, Karan; Bowyer, Duncan (CRC Press, 2023)
"Principles and Practicalities of ENT is a comprehensive resource allowing both students and doctors of all levels to approach common clinical scenarios encountered in ENT with confidence. Each section will take you through how to prepare for patients, key points in the history and examination, and how best to investigate and manage a wide variety of common ENT presentations and conditions. The material is structured to provide an easy reference including red flag and primary care sections to enable readers to know what to look out for when considering referrals. Therefore, in addition to being a great revision tool for medical students, doctors pursuing MRCS (ENT) examinations and higher surgical training in ENT, this book can also serve as a useful aid for primary care physicians in their everyday diagnostics and referral practices"--